2022
DOI: 10.1093/rpsppr/rqac003
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, design and strategies for efficient nanotechnology-based nasal delivery systems

Abstract: Objectives Nanotechnology-based nasal delivery systems have gained interest as a way of overcoming low drug bioavailability, limited brain exposure, fast metabolism and elimination, high doses, and unwanted side effects. The main benefits of intranasal administration include the non-invasive method, easy accessibility, porous epithelial barrier and highly vascularized tissue. However, it is imperative to identify interactions between the materials used and the nasal biological environment to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 147 publications
0
5
0
Order By: Relevance
“…The osmolarity of this formulation was 300 ± 0.8 mOsm/kg in the range of 285–310, which indicated an isotonic solution suitable for nasal preparation ( USP , Ehrick et al, 2013 , Barros et al, 2022 ). The viscosity of the nasal spray formulation was 12.04 ± 2.64 cP at the shear rate of 50 s −1 .…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The osmolarity of this formulation was 300 ± 0.8 mOsm/kg in the range of 285–310, which indicated an isotonic solution suitable for nasal preparation ( USP , Ehrick et al, 2013 , Barros et al, 2022 ). The viscosity of the nasal spray formulation was 12.04 ± 2.64 cP at the shear rate of 50 s −1 .…”
Section: Resultsmentioning
confidence: 84%
“…The local pH value inside the nasal cavity directly influences the rate and extent of drug absorption. It has been suggested that the optimum pH value of nasal spray should range from 4.5 to 6.5 ( Dhakar et al, 2011 ) or 5.5 to 6.5, which is close to the physiological pH ( Barros et al, 2022 ). The pH value of the nasal spray formulation in this current study was 6.02 ± 0.02, which is suitable for nasal epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, even if localization to the olfactory region is achieved, degradation or clearance of the drug must be avoided for successful absorption across the epithelium. A potential formulation strategy that may overcome some of the hurdles of NTBDD is the use of nanocarriers, which, depending on the type of particle, have a number of possible advantages over traditional formulations including improved drug stability, prolonged residence time, controlled release, decreased dosing frequency, and facilitated transport. There have been numerous reports of nanocarriers for NTBDD including liposomes, nanostructured lipid carriers, , solid lipid nanocarriers, , nanoemulsions, , and polymeric nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…A potential formulation strategy that may overcome some of the hurdles of NTBDD is the use of nanocarriers, which, depending on the type of particle, have a number of possible advantages over traditional formulations including improved drug stability, prolonged residence time, controlled release, decreased dosing frequency, and facilitated transport. There have been numerous reports of nanocarriers for NTBDD including liposomes, nanostructured lipid carriers, , solid lipid nanocarriers, , nanoemulsions, , and polymeric nanoparticles. For the latter, a number of polymers have been utilized including natural polymers such as alginate and chitosan as well as synthetic polymers such as poly­(lactic acid), polycaprolactone, and poly­(lactic- co -glycolic acid) (PLGA) .…”
Section: Introductionmentioning
confidence: 99%
“… 31 Based on nanotechnology, pulmonary delivery of therapeutics is facile using various formulations of nasal sprays, solutions, nebulizers, or gels. 32 , 33 Pulmonary delivery of curcumin offers several advantages, such as direct delivery of high drug concentration to the location of the infection, immediate curcumin connection with the SARS-CoV-2 virus, instant deposition into the lower airways and alveolar part, and reduced intra- and extracellular detox actions of enzymes in the respiratory tract. 21 …”
Section: Introductionmentioning
confidence: 99%